2022
DOI: 10.5498/wjp.v12.i9.1261
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium may be an effective therapy for Alzheimer’s disease

Abstract: Magnesium deficiency in serum or the brain of Alzheimer’s disease (AD) patients has been shown to be associated with AD. Current research suggests that supplementing or restoring magnesium may be a novel approach to AD treatment. However, the physiological properties of magnesium make such treatment difficult. It is undeniable that magnesium may be an effective therapy for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, although patients suffering from AD have lower magnesium concentrations, their deficiency levels cannot be accurately evaluated. Slutsky et al reported that after longterm supplementation, the Mg 2+ concentration in cerebrospinal fluid increased only by 15% [93]. The blood-brain barrier keeps at bay the daily fluctuations in blood magnesium and their possible impact on the brain tissue.…”
Section: Magnesium (Mg)mentioning
confidence: 99%
“…However, although patients suffering from AD have lower magnesium concentrations, their deficiency levels cannot be accurately evaluated. Slutsky et al reported that after longterm supplementation, the Mg 2+ concentration in cerebrospinal fluid increased only by 15% [93]. The blood-brain barrier keeps at bay the daily fluctuations in blood magnesium and their possible impact on the brain tissue.…”
Section: Magnesium (Mg)mentioning
confidence: 99%
“…The synapses in hippocampus are quite sensitive to the fluctuations in magnesium concentration. Therefor an increase in half of magnesium concentration wills double the density of synapse [14]. Hypomagnesaemia is a potential risk factor for dementia, hypertension, cerebrovascular accidents, and thrombotic plaques [15].…”
Section: Introductionmentioning
confidence: 99%